2007
DOI: 10.1152/jn.00109.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 5-HT1A- and GABABReceptor Function in Dorsal Raphé Neurons Upon Chronic Fluoxetine Treatment of Socially Stressed Rats

Abstract: Cornelisse LN, Van der Harst JE, Lodder JC, Baarendse PJ, Timmerman AJ, Mansvelder HD, Spruijt BM, Brussaard AB. Reduced 5-HT 1A -and GABA B receptor function in dorsal raphé neurons upon chronic fluoxetine treatment of socially stressed rats. J Neurophysiol 98: 196 -204, 2007. First published April 25, 2007; doi:10.1152/jn.00109.2007. Autoinhibitory serotonin 1A receptors (5-HT 1A ) in dorsal raphé nucleus (DRN) have been implicated in chronic depression and in actions of selective serotonin reuptake inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 66 publications
9
37
1
1
Order By: Relevance
“…The present data indicate that the mechanisms underlying the impairment of coping mechanisms by galanin, although partially related to disturbances in 5-HT neurotransmission, cannot be directly related to changes in 5-HT 1A autoreceptor functions. In agreement, a recent paper has shown that the effects of chronic fluoxetine treatment in socially stressed rats is not associated with downregulation of the 5-HT 1A receptor function in the DR neurons (Cornelisse et al, 2007).…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depressupporting
confidence: 86%
“…The present data indicate that the mechanisms underlying the impairment of coping mechanisms by galanin, although partially related to disturbances in 5-HT neurotransmission, cannot be directly related to changes in 5-HT 1A autoreceptor functions. In agreement, a recent paper has shown that the effects of chronic fluoxetine treatment in socially stressed rats is not associated with downregulation of the 5-HT 1A receptor function in the DR neurons (Cornelisse et al, 2007).…”
Section: Integrative Mechanism Of Galanininergic Regulation Of Depressupporting
confidence: 86%
“…In addition, many studies suggest that increases in adult neurogenesis after the SSRI administration require the activation of 5-HT 1A receptors (Santarelli et al, 2003), which is consistent with the results that 5-HT 1A receptor antagonists or knockout mice decrease or lack cell proliferation in the dentate gyrus, respectively (Radley and Jacobs, 2002;Santarelli et al, 2003). Furthermore, it has been reported that the antidepressant effect of SSRIs are mediated by 5-HT 1A receptors (Tatarczynska et al, 2002;Hirano et al, 2002) by changing the receptor-medicated Gprotein-coupled inwardly rectifying potassium (GIRK) currents (Cornelisse et al, 2007). Therefore, 5-HT 1A is definitely involved in depression as well as the action of antidepressants.…”
Section: Serotonin and Its Receptors In Depressionsupporting
confidence: 83%
“…Several possible mechanisms have been implicated in 5-HT 1A autoreceptor desensitization [42] including uncoupling from G-proteins [41,[47][48][49][50], receptor internalization [51], G-protein inactivation [52] and reduction in 5-HT 1A autoreceptors [38,53]. In addition, coupling to the GIRK is reduced upon chronic fluoxetine treatment [54], one mechanism that may disinhibit raphe firing and allow for enhanced 5-HT neurotransmission. However, these mechanisms of rapid desensitization do not account for the chronic treatment required for antidepressant effects, and are also rapidly reversible [51].…”
Section: -Ht 1a Autoreceptors As Brakes For 5-ht Neurotransmissionmentioning
confidence: 99%